2018
DOI: 10.3748/wjg.v24.i3.371
|View full text |Cite
|
Sign up to set email alerts
|

Multi-parameter gene expression profiling of peripheral blood for early detection of hepatocellular carcinoma

Abstract: AIMIn our previous study, we have built a nine-gene (GPC3, HGF, ANXA1, FOS, SPAG9, HSPA1B, CXCR4, PFN1, and CALR) expression detection system based on the GeXP system. Based on peripheral blood and GeXP, we aimed to analyze the results of genes expression by different multi-parameter analysis methods and build a diagnostic model to classify hepatocellular carcinoma (HCC) patients and healthy people.METHODSLogistic regression analysis, discriminant analysis, classification tree analysis, and artificial neural n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Xie ( 40 ) utilized gene expression profiles from peripheral blood to develop an artificial neural network (ANN) model that could differentiate HCC patients from the control group with a sensitivity of 96% and specificity of 86%. Harpreet ( 41 ) utilized a large-scale transcriptomic analysis dataset containing a total of 2,316 HCC samples and 1,665 non-tumor tissue samples to identify HCC samples using machine learning, with an accuracy ranging from 93% to 98%.…”
Section: Discussionmentioning
confidence: 99%
“…Xie ( 40 ) utilized gene expression profiles from peripheral blood to develop an artificial neural network (ANN) model that could differentiate HCC patients from the control group with a sensitivity of 96% and specificity of 86%. Harpreet ( 41 ) utilized a large-scale transcriptomic analysis dataset containing a total of 2,316 HCC samples and 1,665 non-tumor tissue samples to identify HCC samples using machine learning, with an accuracy ranging from 93% to 98%.…”
Section: Discussionmentioning
confidence: 99%
“…PFN1 was mainly responsible for the polymerization of actin filaments and responds to extracellular signals, which were associated with cell proliferation and motility ( Witke, 2004 ). Xie et al (2018) suggested that PFN1 was a risk factor for poor prognosis in HCC. This was consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the aforementioned single-factor analysis, a multi-factor analysis approach can establish a higher diagnostic value (Ning et al, 2021). Xie et al (2018) constructed an expression detection system based on the GeXP system for nine genes: GPC3, HGF, ANXA1, FOS, SPAG9, HSPA1B, CXCR4, PFN1, and CALR. The team developed a multi-parametric gene expression analysis method by combining logistic regression analysis, discriminant analysis, classification trees, and DNNs to model the diagnosis of groups of earlystage HCC patients and healthy controls by routinizing the area under the curve (AUC), sensitivity, and specificity.…”
Section: Serologymentioning
confidence: 99%